PENGEMBANGAN BAHAN AJAR INTERAKTIF PADA MATA PELAJARAN TEKNIK INSTALASI TENAGA LISTRIK - Nurhadi, Akhmad Roni (Edu Elektrika Journal, 2014)
Improvement and development of the quality of education is an issue that is always demanding attention. Absorption rates subjects received between students with each other is different, there are no high-low berkemampuannya. This is a challenge for teachers to be able to maximize the absorption of each student. The problem in this research is how to plan, create or produce, and test the software in the form of interactive teaching materials for teaching engineering subjects power installations with macromedia flash and whether use of interactive teaching materials suitable for use in the SMK. The research objective to be achieved is to plan, create or produce, and test the software shaped interactive teaching materials to aid learning in subject matter presentation "Power Installation Techniques" at SMK. Data collection techniques used in this study with the completion of interviews, documentation, and questionnaires / checklist. Test results overall instructional media respondents, from multimedia expert stated 84.30% by both criteria, 81.79% of the teachers stated by both criteria, of the students in the two variables, the variable response of the students stating 78.19% by both criteria and variable 77.04% student attitudes expressed by both criteria. Test results to all respondents said this interactive teaching materials fit for use as teaching materials in vocational and has met with success indicators percentage average of 81.23% or better category. Program materials should be used as supplementary teaching materials for engineering subjects power installations. Need further research based on the development of electronic learning materials program with other models as an extra means of learning.